#TITLE_ALTERNATIVE# - A. ANDRE MAILOA (NIM : 10210026); Pembimbing : Dr. Eng. Ferry Iskandar, CH.
Lithium Iron Phophate or LiFePO4 is a material which promising to used as cathode material lithium-ion batteries. However, low electronic and ionic conduc-tivitiy ability cause the spesific capacity that can produced is more lower from theory. Li2SiO3 known have electronic conductivity ~10-4 S/cm and ionic conduc-tivity 10-6 S/cm which is expected to increase spesific capacity of LiFePO4 when used at high current densities or power. LiFePO4/Li2SiO3 is synthesized using hydrothermal method by varying the weight percent (wt%) of Li2SiO3. From the XRD result, pure LiFePO4 is synthesized without any impurities material. When Li2SiO3 was added more, the particle size of crystalline will increase and the crystallinity will decrease. From FTIR result, there is P-O and Fe-O bond vibration which indicate the presence of LiFePO4 and the appearance of [O-Si-O]- and Si-O-Si bonds is indicate the presence Li2SiO3. By using two electrode sys-tem, the EIS of the samples is characterized. The impedance value will increase when Li2SiO3 is added, but if Li2SiO3 added more, the impedance will decrease again. In this research, the impedance value for LiFePO4 is optimal when 5wt% of Li2SiO3 is added. Therefore, further research needs to be done to number of Li2SiO3 which added to LiFePO4 less than 5wt% to get the optimum value ad-dition Li2SiO3.